Government Actions and Their Relation to Resilience in Healthcare; What We See Is Not Always What We Get; Comment on “Government Actions and Their Relation to Resilience in Healthcare During the COVID-19 Pandemic in New South Wales, Australia and Ontario, Canada” - Ian P. Leistikow; Roland Bal (International Journal of Health Policy and Management, 2022)
This commentary reviews the publication by Smaggus et al published in the IJHPM in July 2021 on “Government Actions and Their Relation to Resilience in Healthcare During the COVID-19 Pandemic in New South Wales, Australia and Ontario, Canada” which analysed media releases to identify how governments contributed to resilience in healthcare (RiH). We suggest media releases might not be the best data to capture the mechanisms, activities and interactions through which government actions enhance or hinder RiH. RiH recognizes healthcare as a complex sociotechnical system, so studies into fostering capacity for RiH should be designed for complex sociotechnical systems. This means data should be derived from multiple sources to allow for diverse perspectives, and preferably include direct observations to capture the intricacies of backstage interactions.